Assessment of the level of mental psychomotor abilities according to the charlop-Atwell test for kindergarten children of age groupe (4 -5 years) - Koulougli, Hassina; Ould Hamou, Mostefa; Zeroual, Mohamed (Journal of Human Sciences, 2023)
The aim of this study is to estimate the level of psychomotricity in children aged 4 to 5 years according to the Charlop-Atwell test, which enriches the tools for assessing psychomotor development. For this used the test according to the rating sheet of the Scale of Charlop-Atwell, which contains 06 items for each item has its objective score, subjective score and total score, applied on a sample of 16 children who are at the "Squirrel" crèche with an average age of (4.5-0.52 years) , divided as follows: 4-year-olds (No.08) ( 04 Boys / 04 Girls), 5-year-olds (No.08) (03 Boys / 05 Girls). Analysis of the data showed us that the sex factor does not influence the psychomotricity of children aged 4 to 5 according to the Charlop-Atwell test, but the age factor showed us that there is a significant difference in psychomotricity between 4-year-old girls and 5-year-old girls from P-0.05.